The Influence of Sica Box Three-Dimensional Learning Media on Students' Learning Outcomes in Science Content - Rahilah, Nihayatur; Sofianto, E.W.N (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
The light material and its nature using simple media in science found that students' activeness and understanding decreased causing the low value obtained on the material so that this did not happen, innovation was carried out with the learning media used, namely Sica Box. The aim of the study was to find out the results of students before and after using the media and the effect of the occurrence of sica box media on student outcomes. This research uses quantitative methods with quasi-experiments. Research design with pretest-posttest control Group Design by taking data from 57 students with samples using saturated sample techniques. Calculation of data with the normality test, homogeneity, t-test, and u-test as well as the average, standard deviation, and variance. The results obtained before using the media were 68.39 and after using the media the results were 87.68. It can be seen that there was an increase in student learning outcomes with the values obtained using the sica box media. Furthermore, the calculation of the u test Zcount < -Ztable, namely -5.75 < -1.96, with this Ha is accepted and H0 is rejected, it is found that there is an effect of using sica box media on the learning outcomes of students. The implication of the research is that Sica Box helped master the concept of light.